DEVELOPMENT OF VISUAL AUDITORY KINESTHETIC LEARNING MODEL BASED ON LOCAL WISDOM TO INCREASE THE COMPETENCY OF PROSPECTIVE TEACHERS IN LITERATURE - Artha, Dewi Juni; Febriyana, Mutia; Sitompul, Dian Novianti (Jurnal As-Salam, 2023)
Writing is one of the skills that everyone must have, especially UMSU English Department students as prospective teachers. This research was conducted to develop visual, auditory, and kinesthetic learning models based on local wisdom to improve prospective English teachers’ skills in the literature field. This research aims to present the results of the VAK learning model based on local wisdom to improve prospective English teachers’ literature skills through writing literary works, especially fairy tales. The research method used to develop a VAK learning model based on local wisdom is research and development, with the 4RD model development process. The data collection techniques used were interviews, observation, and instruments. The data analysis technique used is quantitative descriptive analysis. The results of the validity assessment show that the average score achieved was 92/100 points. The percentage of teachers responding to the application of teaching materials was 93.7%. With the results achieved, the development of this learning model is very reasonable and applicable. The results of activities implementing the VAK learning model based on students’ local intelligence in writing literary works reached an average of 89.8%. In other words, the learning model above is good and can be used.